Identification, quantification and validation of stigmasterol from Zingiber cassumunar Roxb using high-performance thin layer chromatography method - AKSHADA AMIT KOPARDE; ANUP A.PATIL; DR.R.C.DOIJAD; DR.C.S.MAGDUM (International Journal of Pharma and Bio Sciences, 2019)
The idea of characterization of bioactive fractions from the rhizomes of Zingiber cassumunar Roxb is the main objective of this research. The present study is designed to develop a new simple, precise, rapid and selective highâ€performance thinâ€layer chromatographic (HPTLC) method for the determination of stigmasterol in dichloromethanolic rhizomes extract of Zingiber cassumunar Roxb. This study presents the first report of HPTLC method, which has been developed and validated for quantification of the one marker compounds (stigmasterol) from dichloromethanolic extract using the solvent system of Chloroform:dichloromethane (5.4:11.2). According to the guidelines of ICH , different concentrations of standard stigmasterol was applied on 5rHPTLC plates for the quantification of stigmasterol as active fraction from the rhizomes. The concentration of standard stigmasterol is 1 mg/ml. The retention factor of stigmasterol was 0.43. Linearity was obtained in the range of 80 ngâ€280 ng for stigmasterol. The linear regression data for the calibration plots showed a good linear relationship with correlation coefficient =99.57% and coefficient of variation =3.76695% for stigmasterol. The results obtained in validation assays indicated the accuracy and reliability of the developed HPTLC method for the quantification of stigmasterol in dichloromethanolic rhizomes extract of Zingiber cassumunar Roxb. The method was validated for linearity, precision, specificity and it was found to be precise, reliable, and suitable. The proposed method is simple, rapid, precise and accurate. The method was found to be suitable for qualitative and quantitative analysis of stigmasterol in the dichloromethanolic extract of Zingiber cassumunar Roxb.